Dropout in postgraduate programs: a underexplored phenomenon. A scoping review (2024)
Postgraduate education has become increasingly crucial for nations in recent years,contributing to scientific, technological, and social progress. However, high dropoutrates may undermine the benefits of postgraduate education. This study aims to iden-tify which individual, academic, socio-economic, and institutional variables influencestudent attrition at the postgraduate level (master’s and doctoral) through a scopingreview. Using the PRISMA-ScR method, we analyzed 40 research articles for bibliomet-ric insights and specifically examined explanatory variables for postgraduate dropout.Within the individual determinant, explanatory variables include nationality, gender,age, marital status, family support, family and work obligations, and motivation levels.Socio-economic variables encompass the student’s income, employment status, andthe national macroeconomic environment. In the academic context, key variablescomprise prior knowledge, academic performance, student satisfaction, autonomy,self-efficacy, and research interest. Lastly, variables such as insufficient financial resour-ces, institutional policies, teacher-student interaction, student support, academic infra-structure, and curriculum design play pivotal roles in the institutional realm. Inconclusion, this study enhances our understanding of postgraduate dropout, offeringvaluable insights for the academic community and States to develop strategies thatimprove retention rates and reduce dropout levels in postgraduate education